Identification of a core-periphery structure among participants of a business climate survey - Ulrich Stolzenburg; Thomas Lux (Kiel Institute for the World Economy (IfW), 2010)
Processes of social opinion formation might be dominated by a set of highly influential agents acting as 'opinion leaders'. Here we explore whether such a perspective could shed light on the dynamics of a well known economic sentiment index. To this end, we hypothesize that the respondents of the survey under investigation form a core-periphery network, and we identify those agents that define the core (in a discrete setting) or the proximity of each agent to the core (in a continuous setting). As it turns out, there is significant correlation between the so identified cores of different survey questions. Both the discrete and the continuous cores allow an almost perfect replication of the original series with a reduced data set of core members or weighted entries according to core proximity. Using a monthly time series on industrial production in Germany, we also compared experts' predictions with the real economic development. The core members identified in the discrete setting showed significantly better prediction capabilities than those agents assigned to the periphery of the network.
Keywords: C42; C83; D85; 330; Business climate; network topology; economic expectations; Geschäftsklima; Erwartungstheorie; Soziales Netzwerk; Kern-Peripherie-Beziehung; Schätzung; Deutschland